Key research themes on ICT and sustainable urban mobility. Issue 1 (2nd January 2016) - Cohen-Blankshtain, Galit; Rotem-Mindali, Orit
Abstract: Information and communication technologies (ICTs) are hypothesized to replace or change the use of the transport system by facilitating new or different activities. This article offers a review of more than 40 years of research regarding the relationship between ICTs and urban mobility. We discuss the expectations for the changes in travel demand, travel patterns, and the urban form as a result of the development and introduction of ICTs. Much of the interest in the relationships between ICTs and mobility is premised on the expectation of substitution effects, but empirical findings often suggest more complex effects than direct substitution. Although research on single types of travel activity may sometimes indicate simple substitution effects, examination of the broader impacts may also reveal travel generation effects as well. As such, ICTs do not simply substitute mobility patterns but change them. A growing body of research focuses on changing mobility patterns (in terms of time and space), changes in the experience of travel and changes in the perceptions of travel costs due to the interaction between old and new technologies for overcoming distance. ICTs are gradually becoming embedded within the transport system, enabling flexibility, multitasking, and an increase in human activities.